-26=6(v-6)-8v

Simple and best practice solution for -26=6(v-6)-8v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26=6(v-6)-8v equation:


Simplifying
-26 = 6(v + -6) + -8v

Reorder the terms:
-26 = 6(-6 + v) + -8v
-26 = (-6 * 6 + v * 6) + -8v
-26 = (-36 + 6v) + -8v

Combine like terms: 6v + -8v = -2v
-26 = -36 + -2v

Solving
-26 = -36 + -2v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '2v' to each side of the equation.
-26 + 2v = -36 + -2v + 2v

Combine like terms: -2v + 2v = 0
-26 + 2v = -36 + 0
-26 + 2v = -36

Add '26' to each side of the equation.
-26 + 26 + 2v = -36 + 26

Combine like terms: -26 + 26 = 0
0 + 2v = -36 + 26
2v = -36 + 26

Combine like terms: -36 + 26 = -10
2v = -10

Divide each side by '2'.
v = -5

Simplifying
v = -5

See similar equations:

| x/4+10=-2 | | 12=y+4 | | 6x-4=2x+28 | | 3xsquared-150x-1200=600 | | -13.00x+2.00=8 | | E+6-1=3 | | 2.3=4.5X+30.2 | | -13.00+2.00=8 | | y=15x+27 | | 0.05-0.6x=5.3 | | (2ax+bx)(2ax+bx)= | | R-3.5=-2.1 | | 15=5+y | | 32x^3+13x^3+23x^4= | | 32x^3+13x^3+13x^3= | | 8x-9=3x+-16 | | 6[x+4]=36 | | 6(-17-3y)+2y=10 | | (x+2y)2= | | mx^2+(m-1)x-3=0 | | 130+2x+10=180 | | 4b+7=1b+15 | | 13/19+6y=9 | | 3x^2-27x-30=0 | | 2(x+2)=2x | | 51x^5+119x^9+221x^10= | | 12a+11b+2c+4c-5b-2a= | | -10+7y+6y=9 | | 0.05x-0.6=52 | | 20p+15q+p-4p-5p= | | 3x-3=4y-4 | | 5x-20=6x-40 |

Equations solver categories